Potensi Lada Hitam Sebagai Obat Herbal Terstandar Untuk Disfungsi Ereksi: Literature Review - Hasbullah, Faza; Hadibrata, Exsa; Mayasari, Diana (Medula, 2024)
Erectile dysfunction (ED) is a condition that affects men of all ages and backgrounds, characterized by the inability to achieve or maintain an erection sufficient for sexual intercourse. First-line treatments for ED, such as Phosphodiesterase-5 Inhibitors (PDE5i), often cause side effects and pose contraindications, especially for patients with cardiovascular diseases. Consequently, various studies have been conducted to explore safer natural remedies. One natural substance proven to enhance erectile function is black pepper. This study implement a literature review approach, examining articles from scientific databases published between 2011 and 2025. Piperine, the active compound in black pepper, exhibits significant antioxidant and anti-inflammatory effects, reduces TNF-α levels, and protects nitric oxide (NO) from free radicals. Piperine also enhances testosterone levels by stimulating Leydig cells, contributing to improved erectile function. Moreover, piperine has been shown to increase the expression of the StAR gene, which plays a critical role in testosterone biosynthesis, essential for the erection process. Studies on animal models demonstrated improvements in sexual behavior, testosterone levels, and total penile reflex following black pepper extract administration. Black pepper holds potential as a natural therapy for ED through mechanisms involving increased NO activity, modulation of testosterone hormones, and protection of Leydig cells. While results from animal studies are promising, further research on humans is required to confirm its efficacy and safety.